2017
DOI: 10.1016/j.celrep.2017.03.062
|View full text |Cite
|
Sign up to set email alerts
|

How a Mutation that Slows Aging Can Also Disproportionately Extend End-of-Life Decrepitude

Abstract: Summary The goal of aging research is to extend healthy, active life. For decades, C. elegans daf-2 insulin/IGF-1 receptor mutants have served as a model for extended lifespan and youthfulness. However, a recent report suggested that their longevity is associated with an undesirable phenotype: a disproportionately long period of decrepitude at the end of life. In a human population, such an outcome would be a burden to society, bringing into question the relevance of daf-2 mutants as a model for life extension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
135
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(145 citation statements)
references
References 30 publications
(34 reference statements)
8
135
1
Order By: Relevance
“…(2015) and Hahm et al. (2015) did not include intermediate movement phenotypes, but other recent studies observed that an extended intermediate movement behavior was characteristic of both long‐lived mutants as well as long‐lived worms in wild‐type background (Churgin et al., 2017; Podshivalova et al., 2017; Zhang et al., 2016). Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(2015) and Hahm et al. (2015) did not include intermediate movement phenotypes, but other recent studies observed that an extended intermediate movement behavior was characteristic of both long‐lived mutants as well as long‐lived worms in wild‐type background (Churgin et al., 2017; Podshivalova et al., 2017; Zhang et al., 2016). Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Podshivalova et al. (2017) show that an extended period of reduced movement in daf‐2 mutants is due to enhanced resistance to bacterial colonization that leads to premature death in wild‐type animals. The observations for other long‐lived mutants may be explained by a similar survivor benefit, a trade‐off between fitness and longevity, or inappropriate activation of the dauer pathway (Arantes‐Oliveira, Berman, & Kenyon, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations